The impact of workplace spirituality and employees' wellbeing at the industrial sector: the Nigerian experience. (2013)
In this 21st century when the world economy has been globalised, organizations are faced with more complexities, competition and structural changes which elicit the introduction of spirituality within the workplace so as to enable human hearts, spirits and souls to grow and flush so that employees and employers will become healthy, creative, innovative, compassionate and productive in all endeavors to the sustenance of the workplace. The study examined the impact of workplace spirituality on employees' wellbeing at the industrial sectors. The descriptive survey research design of the ex-post-facto type was used for the study. A total of two hundred and seventy - five (275) participants were involved in the study. The participants were drawn from three firms representing three industrial sectors (Food & Beverages, Publishing, Agro allied) in Oyo state, Nigeria. While spirituality at work is an abstract concept, this empirical finding showed that each of the three dimensions of spirituality at workplace (meaningful work, purposeful work, and sense of community/interconnectedness) has positive significant impact on the wellbeing of employees'. The study recommended that Management, Human resource personnel, Industrial Social Workers should be at alert to take into account employees spiritual lives and the value and richness of their collective potential for the wellbeing of employees and the sustainance of the workplace.